Is there an environmental benefit to being an exporter? Evidence from firm level data - Svetlana Batrakova; Ronald B. Davies (University College Dublin, UCD School of Economics, 2010)
One of the greatest concerns over globalisation is its impact on the environment. This paper contributes to this debate by analysing the consequences of becoming an exporter on a firm's energy consumption. We show both theoretically and empirically that for low fuel intensity firms exporting status is associated with higher fuel consumption while for high fuel intensity firms exporting is results in decreased fuel consumption. Further analysis reveals that higher fuel consumption of low fuel intensity firms occurs after exporting, perhaps as a response to increased production. In contrast, firms using relatively large quantities of fuel decrease their energy use after exporting, perhaps by adopting more fuel-effcient technology. These results indicate that the use of aggregate data, as is the case in almost all studies of trade and the environment, is likely to conceal important connections between the two.
hdl:10197/2638
Keywords: F18; L23; Q56; C21; 330; Exporting; Energy; Heterogeneity; Quantiles; Matching